2022
DOI: 10.1038/s41598-022-17225-9
|View full text |Cite|
|
Sign up to set email alerts
|

A non-randomized, open-label study of the safety and effectiveness of a novel non-pneumatic compression device (NPCD) for lower limb lymphedema

Abstract: Lower extremity lymphedema (LEL) can result in detriments to quality of life (QOL) and impose a significant economic burden on patients and payers. A common component of treatment is pneumatic compression, which requires patients to remain immobile. We investigated a novel non-pneumatic compression device (NPCD) that allows patients to remain active during compression treatment, to see if it reduces swelling and improves QOL. We conducted a non-randomized, open-label, 12-week pilot study of adult patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…21,22 However, APCDs are bulky, nonportable medical equipment that are cumbersome to use, with reported poor adherence. 23 More recently, clinical studies [25][26][27] involving an NPCD have reported an approach that encompasses multiple established treatment modalities and shows early promise of improved clinical efficacy, quality of life, and patient adherence.…”
Section: Gradient Sequential Compressionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,22 However, APCDs are bulky, nonportable medical equipment that are cumbersome to use, with reported poor adherence. 23 More recently, clinical studies [25][26][27] involving an NPCD have reported an approach that encompasses multiple established treatment modalities and shows early promise of improved clinical efficacy, quality of life, and patient adherence.…”
Section: Gradient Sequential Compressionmentioning
confidence: 99%
“…Results from these studies, including a multicentered randomized crossover trial, indicate that the NPCD provided better edema reduction per patient self-reporting, greater edema volume reduction, and increased quality of life and patient satisfaction compared with APCD. [25][26][27]…”
Section: Active Compression Beyond a Single Treatment Modalitymentioning
confidence: 99%
See 2 more Smart Citations